Rating as an indicator of the quality of a teacher’s professional activity - Abeldina, Zh.K.; Moldumarova, Zh.E.; Abildina, G.Sh.; Abeldina, R.K. (KU Publ., 2021)
The article examines several aspects of the quality of educational services. The process of providing such services is examined, the problems in the field of teaching physics and mathematics are identified and the ways of problem resolution in the credit learning system are proposed. The introduction of credit learning technology allows for stimulation of students’ learning activity and an increase in their motivation and the level of academic mobility. The ways of increasing the motivational activity of the teacher as another key figure in the educational process are identified. The current remuneration system for university teachers in Kazakhstan accounts for work experience and the position held and includes additional payments for an academic degree but does not stimulate teachers for continuous additional training. On the other hand, the salary volume does not contribute to the high social prestige of this profession, which is complex and requires genuine pedagogical skills. The quality of teaching staff is associated with the quality of education acquired by students. In the context of the credit rating system, it is not only students who earn credits, but also teachers who should substantiate and improve their qualifications measured by their rating.
Рейтинг оқытушы қызметінің сапасын бағалау көрсеткіші ретінде
Рейтинг как показатель оценки качества деятельности преподавателя
Keywords: forms for determining a teacher’s rating; teaching quality assessment; credit rating system; quality of education; Education; services; motivation activity; professional level